The effect of rinsing time periods on wettability of elastomeric impression materials: in vitro study - Özlem Acar; Selim Erkut (Gazi University, 2016)
OBJECTIVE: The aim of this study was to determine whether different rinsing time periods affected the wettability of polymerized elastomeric impression materials. MATERIALS AND METHOD: Panasil Contact Plus (PCP), Panasil Contact Non-Surfactant (PCNS), Panasil Initial Contact (PIC), Express (EXP) and Impregum (IMP) impression materials were tested. Standardized samples were rinsed with water for 10 s, 15 s or 20 s, and the wettability was determined by contact angle measurement through an evaluation period of 60 seconds (n=7). Non-rinsed groups were used as control. Measurements were made at 5 time points (at 0, 6, 15, 30 and 60 seconds). Kruskal Wallis test and Conover's multiple comparison tests were used for all multiple comparisons. Bonferroni adjustment was applied for controlling Type I error (p<0.002). RESULTS: Rinsing 10 s, 15 s or 20 s significantly reduced the wettability of the impression materials PCP, PIC and EXP (p<0.002). However, wettability of the impression materials PCNS and IMP did not significantly change after rinsing (p>0.002). CONCLUSION: Rinsing the surfactant-containing polyvinylsiloxane impression materials decreased their wettability, whereas no such effect was seen for the surfactant free polyvinylsiloxane and polyether impression materials.